More than just modifications: “The new peruvian customs legislation” - La Noire Núñez, José Antonio (2020)
During the years 2018 and 2019, the Government, fulfilling its role as facilitator of favorable conditions for the competitiveness of Peruvian foreign trade, launched a package of measures that it sought to update the Peruvian Customs Legislation by modifying the General Customs Law and its regulations, table of sanctions applicable to offenses provided for in the general customs law and other Customs Procedures. Through Legislative Decrees, Supreme Decrees and Superintendency Resolutions, it was sought to adapt customs legislation to international standards due to the signing of international agreements that Peru had signed (Riva, 2020). In this way, among the main changes made to the legislation to speed up and ensure the traceability of goods we have that there are 03 different actors and the categorization of Foreign Trade Operators; the obligation of early clearance for the Import regime for consumption; the classification of infractions according to their severity and the updating of various dispatch procedures.